(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study was conducted to evaluate the caregiving burden and to identify factors associated with the caregiving burden among primary caregivers of outpatient Parkinson’s disease patients at Thai Nguyen Central Hospital. Methods: A cross-sectional descriptive study was conducted on 104 primary caregivers from March 2024 to March 2025. Results: The mean Zarit Caregiver Burden Score among participants was 44.0 points. The distribution of caregiving burden levels revealed that the majority of caregivers experienced a moderate burden (62.5%), followed by low burden (20.2%), high burden (13.5%), and no burden (3.8%). Statistically significant associations were observed between the caregiving burden and factors such as disease stage, presence of comorbid chronic illnesses, and duration of illness (p<0.05). Furthermore, better physical health status of caregivers, higher personal income, and a greater number of co-caregivers were inversely correlated with the caregiving burden (p<0.01). Conversely, the amount of time spent on caregiving showed a positive correlation with the caregiving burden (p<0.01). Conclusion: The findings emphasize the urgent need for comprehensive support interventions targeting caregivers, particularly those providing care for patients with advanced and prolonged Parkinson’s disease.